Pengaruh Jumlah Simpanan dan Jumlah Pinjaman terhadap Sisa Hasil Usaha pada Koperasi Unit Desa Mambal, Kecamatan Abiansemal, Kabupaten Badung - DEWI S, PUTRI RAHMAWATI; SUSRUSA, KETUT BUDI; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Effect of the Amount of Deposits and Lending Credit on Profits of Village Unit Cooperatives of Mambal, Sub-District of Abiansemal, Badung Regency Cooperatives are legal entities established by individuals or cooperative legal entities, with the separation of the wealth of their members as capital to run a business to meet common needs. One of the forms of cooperative development is the village unit cooperative. Factors that influence the existence of cooperatives in the midst of the global economy are the amount of net income they have. The Mambal Village Unit Cooperative has carried out several businesses in order to obtain maximum profits. Efforts are made, namely by carrying out activities to raise funds, both from members and from the public in the form of deposits and credits. This study aims to determine the effect of the total of deposits and amount of credits on the profits. This research was conducted at the Mambal Village Cooperative Unit, Abiansemal Sub-District, Badung Regency. This study uses multiple linear regression analysis. The results of the study showed that simultaneously the amount of deposits and the amount of credits had a positive and significant effect on the profits of the Mambal Village Unit Cooperative. Partially the amount of deposits has a positive and significant effect on the profits at the Mambal Village Cooperative Unit, while the amount of credits has a positive and not significant effect on the profits of the Mambal Village Unit Cooperative.